2004
DOI: 10.1046/j.1365-2672.2003.02149.x
|View full text |Cite
|
Sign up to set email alerts
|

The composition and persistence of faecal coliforms and enterococcal populations in sewage treatment plants

Abstract: Aims: The changes in structure and composition of faecal coliforms and enterococcal populations in sewage from different treatment plants, and the elimination of vancomycin-and erythromycin-resistant enterococci (VRE and ERE, respectively) in these treatment plants was analysed to determine any selective reduction. Methods and Results: Faecal coliforms, enterococci, VRE, ERE and spores of sulphite-reducing bacteria were enumerated using standard methods. Samples were enriched where necessary in order to isolat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
35
0
3

Year Published

2005
2005
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 53 publications
8
35
0
3
Order By: Relevance
“…The reutilization of treated sewage or sludge could carry a possible health risk if these antibiotic-resistant bacterial populations persist. The persistence of these VRE and ERE strains in treated sewage has already been demonstrated in previous studies (Vilanova et al, 2004). However, their accumulation or persistence in sludge of the treatment plants is poorly described.…”
Section: Introductionmentioning
confidence: 83%
See 3 more Smart Citations
“…The reutilization of treated sewage or sludge could carry a possible health risk if these antibiotic-resistant bacterial populations persist. The persistence of these VRE and ERE strains in treated sewage has already been demonstrated in previous studies (Vilanova et al, 2004). However, their accumulation or persistence in sludge of the treatment plants is poorly described.…”
Section: Introductionmentioning
confidence: 83%
“…It has been demonstrated that FC and ENT populations have high similarity in composition and structure between raw and treated sewage. Moreover, the predominant species of both bacterial groups are consequently the same (Vilanova et al, 2004) for both kind of sewages. In contrast, a different proportion of these bacterial indicators has been reported when comparing sludge with respect to sewage (Chauret et al, 1999).…”
Section: Introductionmentioning
confidence: 87%
See 2 more Smart Citations
“…Among the processes being carried out in sewage treatment plants to reduce the pathogens are the removal of bacteria by inactivation, grazing by ciliated protozoa and adsorption to sludge solids and/or encapsulation within sludge flocks followed by sedimentation (Bitton 1994). Some sewage treatment plants have reported the presence of faecal coliforms (FC), enterococci (ENT) and spores of sulphite-reducing bacteria (SRB) in treated sludge (Hill and Sobsey 1998;Vilanova et al 2004). …”
Section: Introductionmentioning
confidence: 99%